Knowledge, Attitude and Practices towards the use of Emergency Contraceptive Pills among Females aged 15-25 years in Tororo General Hospital, Tororo District. A Cross-sectional Descriptive Study. - Clinton, Chiria (Student's Journal of Health Research Africa, 2022)
Background: This study aimed to determine the knowledge, attitude, and practices toward the use of emergency contraceptive pills among females aged 15-25 years in Tororo general hospital, Tororo district. The specific objectives of the study were to determine the: knowledge, attitude, and practices towards the use of emergency contraceptive pills among females aged 15-25 years. Methodology: The study employed a descriptive cross-sectional design with a simple random technique as the sampling technique on a sample of 50 respondents. Data was collected using questionnaires with semi-structured and open-ended questions written in the English language; data was later analyzed manually and presented in tables, bar graphs, and pie charts using Microsoft word. Results: Practices towards the use of emergency contraceptive pills showed that the majority (82%) of the respondents preferred having unprotected sex, most (64%) of the respondents have never used emergency contraceptive pills, and among the respondents who have ever used ECPs, most (68%) of them used postinor, most (60%) obtained the ECPs from a pharmacy and more than half (56%) used the ECPs once in a month. Conclusion: Generally, the researcher concluded that the knowledge about emergency contraceptive pills is inadequate. The attitude towards the use of the ECPs is not good since most respondents thought they were unsafe for usage and also thought it was not effective in the prevention of unwanted pregnancies, the practices towards the use of emergency contraceptive pills are also not good since most of the respondents have never used ECPs at all. Recommendation: The researcher recommended that; Tororo general hospital administration should sensitize and create awareness about the use of emergency contraceptive pills to create a better attitude and increase practices toward using the EC.